Private property rights, dynamic efficiency and economic development: An Austrian reply to neo-marxist scholars Nieto and Mateo on cyber-communism and market process - William Hongsong Wang; Victor I. Espinosa; José Antonio Pe\~na Ramos (Economies, 2021)
The Austrian school economics and neo-Marxist theories both have been reviving in recent years. However, the current academic discussion lacks a debate between two schools of economics with diametrically opposed views. This paper is the first and an initial Austrian challenge to Neo-Marxist scholars Nieto and Mateo's argumentation that cyber-communism and the Austrian theory of dynamic efficiency are consistent to enhance economic development. Their argument focuses on two issues: (a) the existence of circular reasoning in the Austrian theory of dynamic efficiency, and (b) dynamic efficiency and full economic development could be strongly promoted in a socialist system through new information and communication technologies (ICT) and the democratization of all economic life. While cyber-communism refers to cyber-planning without private property rights through ICT, dynamic efficiency refers to the entrepreneurs' creative and coordinative natures. In this paper, first, we argue that the hypothesis that dynamic efficiency and cyber-communism is not compatible. Contrary to the above cyber-communist criteria, the Austrian theory of dynamic efficiency argues that to impede private property rights is to remove the most powerful entrepreneurial incentive to create and coordinate profit opportunities. Second, we argue that the cyber-communism system is inconsistent with economic development. In this regard, we explain how the institutional environment can cultivate or stifle dynamic efficiency and economic development. Having briefly outlined the central argument of Nieto and Mateo, we examine the institutional arrangement supporting cyber-communism. After that, we evaluate the implications of cyber-communism in the dynamic efficiency process. It becomes manifest that Nieto and Mateo's accounts are too general to recognize the complexity of how economic development works.
Keywords: 330; Austrian economics; cyber-communism; dynamic efficiency; economic calculation; economic development; entrepreneurship; market process; Neo-Marxism; private property rights; socialism